اثر كفاءة نظم المعلومات التسويقية في اكتساب الميزة التنافسية في الشركات الصناعية الأردنية - د.غالب, محمد البستنجي (Recherches économiques et managériales, 2011)
ملخص تهدف هذه الدراسة لتحديد أثر كفاءة نظم المعلومات التسويقية على اكتساب الميزة التنافسية في الشركات الصناعية الأردنية، ولتحقيق أهداف الدراسة، تم بناء استبانه وتوزيعها على عينة عشوائية بسيطة مكونة من 300 مفردة من المستخدمين لنظم المعلومات التسويقية في الشركات الصناعية، استرجع منها 245 استبانه، أي ما نسبته (81.6%) من العينة. وتوصلت الدراسة إلى أن إدراك المستجوبين لكلٍ من كفاءة نظم المعلومات التسويقية(المتطلبات المادية، البرمجيات، البشرية، والإدارية) وأبعاد الميزة التنافسية (الإبداع والابتكار، السرعة، المرونة، التميز، والجودة) مرتبة حسب أهميتها، كانت مرتفعة، وأشارت النتائج إلى وجود أثر هام ذو دلالة إحصائية لكفاءة نظم المعلومات التسويقية في اكتساب الميزة التنافسية بجميع أبعادها. وتم اقتراح عدد من التوصيات تمكن الشركات من الاستفادة من نظم المعلومات التسويقية بطريقة كفوءة لاكتساب الميزة التنافسية المستدامة. الكلمات الدالة: نظم المعلومات التسويقية، متطلبات نظم المعلومات التسويقية، اكتساب الميزة التنافسية، الميزة التنافسية المستدامة، أبعاد الميزة التنافسية. Abstract       The purpose of this study is to determine the effect of the efficiency of marketing information systems on gaining of the competitive advantage in the Jordanian Industrial Companies. In order to achieve the objectives of this study, a questionnaire was constructed and distributed among the samples study, which consisted of (300) subjects from who used (MISs) in the Industrial Companies , (245) members responded, forming a rate of (81.6%). The results of the study indicate that, the respondents' perception to the each of efficiency of MISs ( physical, software, human and managerial requirements) and dimensions of the competitive advantage (creativity and innovation, speed, elasticity, differentiation and quality), stated according to their importance, and were high.   The results, also, indicate that there is significant statistical effect of the efficiency of the (MISs) on the gaining of the competitive advantage with all it dimensions. Some recommendations were suggested to enables companies to using (MISs) in efficient way to gaining sustainable competitive advantage. Keywords: marketing information systems (MISs), MISs Requirements, gaining of the competitive advantage, sustainable competitive advantage, dimensions of the competitive advantage.